Physical Activity as a Contributing Factor to Cognitive Function and Sleep Quality among Senior High School Adolescents - Finardi, Kalamda Ilman; Rahmi, Upik; Suparto, Tirta Adikusuma (FORIKES, 2026)
Adolescents represent an age group that is particularly vulnerable to declines in cognitive function and disturbances in sleep quality, often associated with low levels of physical activity. This condition has become an increasingly concerning public health issue, as it directly affects students’ learning concentration, memory capacity, and psychological well‑being. The purpose of this study was to examine the relationship between physical activity, cognitive function, and sleep quality among eleventh‑grade students at Sekolah Menengah Atas Negeri 1 Ngamprah. This study employed a quantitative design with a correlational approach and a cross‑sectional framework. A total of 76 students were selected using stratified random sampling. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ), cognitive function was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA‑Ina), and sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using Fisher’s Exact correlation test. The findings indicate a significant relationship between physical activity and cognitive function (p = 0.021), as well as between physical activity and sleep quality (p = 0.007). These results demonstrate that higher levels of physical activity are associated with better cognitive performance and improved sleep quality among adolescents. As conclusion, this study highlights the essential role of physical activity in supporting cognitive function and sleep quality in adolescents. It is recommended that adolescents engage in regular moderate‑to‑vigorous physical activity for at least 150 minutes per week as a promotive and preventive measure against cognitive and sleep disturbances.Keywords: physical activity; cognitive function; sleep quality; adolescents